UV degradation of styrene-butadiene rubber versus high density poly(ethylene) in marine conditions studied by infrared spectroscopy, micro indentation, and electron spin resonance imaging. (October 2018) - Šlouf, Miroslav; Pilař, Jan; Dybal, Jiří; Šloufová, Ivana; Michálková, Danuše; Lukešová, Miroslava; Zgadzai, Oleg; Blank, Aharon; Filippov, Sergey K.
Abstract: UV irradiation and thermal degradation were studied in marine conditions for styrene-butadiene rubber (SBR) and high density poly (ethylene) (HDPE) containing a Tinuvin ® 770 hindered amine stabilizer. Electron spin resonance imaging (ESRI) was used to monitor degradation process in various depths and compare the polymers in terms of robustness to UV irradiation. In addition, both oxidative degradation and mechanical properties were studied by microscale methods, such as infrared microspectroscopy (IR) and microindentation hardness testing (MHI), enabling us to compare the material changes locally, i.e. both at the exposed surfaces and inside the samples. In SBR/Tin770 system, Tinuvin ® 770 stabilizer failed to protect the polymer matrix against photooxidation as clearly seen from IR/ATR spectra. The Weather-Ometer (WOM) aging resulted in strong oxidative degradation of both non-stabilized and stabilized SBR and caused remarkable changes in three regions of IR/ATR spectra. The strong photooxidative degradation was also manifested through the micromechanical properties of SBR/Tin770 systems. The change of the local properties was the same (within the standard deviations) for both stabilized and non-stabilized samples, which confirmed negligible stabilization efficiency of Tinuvin ® 770 in the SBR system. In contrast to the SBR systems, similar experiments showed very dramatic stabilization effects in the HDPE/Tin770 system. ESR and 2D spectral-spatial ESRI directly proved the different degradation behavior of the two types of the composites: whereas in the SBR composites fast degradation was observed, high density poly (ethylene) showed much slower degradation. We attributed such striking difference to the modification of Tinuvin ® 770 hindered amine stabilizer after vulcanization during preparation of SBR rubber, which apparently eliminated most of its protective activity. Highlights: Degradation of styrene-butadiene rubber (SBR) and high density polyethylene (HDPE) with Tinuvin ® 770 stabilizer were studied. In SBR/Tin770 system, Tinuvin ® 770 stabilizer failed to protect the polymer matrix against photooxidation. In contrast to the SBR systems, similar experiments showed very dramatic stabilization effects in the HDPE/Tin770 system. ESR and 2D spectral-spatial ESRI directly proved the different degradation behavior of the two types of the composites. The difference is attributed to change of Tinuvin ® 770 during SBR preparation, which limited most of its protective activity.